Felid Furs and Bird Feathers: New Interactions Emerging between Homo sapiens and the Animal Kingdom during the Southern African Middle Stone Age - (:unkn) unknown (My University, 2023)
In southern Africa, data on hunter-gatherers’ exploitation of small prey (i.e. carnivores, birds, reptiles, and small mammals) are rare. Here, I propose a synthesis of results obtained from the taphonomic and zooarchaeological analyses of carnivore and bird remains from, respectively, Diepkloof Rock Shelter on the West Coast of South Africa, and Sibhudu Cave, next to the Indian Ocean coastline on the eastern part of the country. In both cases, the taphonomic data support the hypothesis that humans accumulated at least part of the faunal remains. The occurrence of cut-marks on several specimens demonstrates the anthropogenic exploitation of felids at Diepkloof and of Columbidae, Galliformes and several Afromontane evergreen forest bird taxa at Sibhudu. The cut-mark patterning suggests the extraction of felid furs and the consumption of birds for their meat and possibly their feathers. Such practices highlight new forms of interactions between anatomically modern human groups and the animal kingdom during the Late Pleistocene. They develop in a context of cultural bourgeoning in southern Africa characterized by numerous technological innovations and the emergence of symbolic practices at the end of marine isotopic stage (MIS) 5, from ca. 100,000 years, and throughout MIS 4.
Keywords: African Research